IMPACT OF BIODIESEL AGROINDUSTRY ON THE ACHIEVEMENT OF NATIONAL ENERGY SECURITY - Alfa Firdaus; Machfud Machfud; Ani Suryani; Noer Azam Achsani (Universitas Mercu Buana, 2020)
The National Energy General Plan (RUEN) has set 11.6 million kiloliters of biodiesel production target in 2025. The determination of biodiesel production targets in RUEN is part of the objectives mandated in the National Energy Policy (KEN), which is to achieve energy security and independence. Therefore, this study aims to analyze the impact of biodiesel agroindustry on the achievement of national energy security in 2025. The simulation conducted in this study uses Long-range Energy Alternatives Planning (LEAP) software, which based on the accounting model. The model has run on Business as Usual (BAU) scenario, using four dimensions and 12 indicators of energy security in the context of biodiesel agroindustry. Model simulation results show a decreasing energy security trend in the period of 2022-2025, while the biodiesel production target, which was set at RUEN, cannot be achieved in 2025. This is mainly related to availability and affordability, which experienced a decline in the period. Further research needs to be done on the strategy of developing biodiesel agroindustry by considering scenarios of increasing production capacity and productivity as well as its impact on national energy security.